HEMATOLOGY OF Pangasianodon hypophthalmus THAT WERE FED WITH CONTAINING FERMENTED RED GINGER (Zingiber officinale var. Rubrum) TO PREVENT THE Motile Aeromonas Septicaemia DISEASE - Pulungan, Listi Agustina; Riauwaty, Morina; Luskityowati, Iesje (Asian Journal of Aquatic Sciences, 2022)
Red ginger is a natural ingredient that has antibacterial compounds. This research was conducted from June to August 2021 at the Fish Disease and Parasite Laboratory, Department of Aquaculture, Faculty of Fisheries and Marine, Universitas Riau, Pekanbaru. The aim of this study was to obtain the best dose of fermented red ginger added to the feed on the hematology of striped catfish. The method used is an experimental method using one factor Completely Randomized (CRD) with five treatment levels and three replications. The treatments applied were Kn: negative control (no treatments), Kp: positive control (no treatments and infected with A. hydrophila), P1 (150 mL/kg of feed and tested against A.hydrophila, P2 (175 mL/kg of feed), P3 (200 mL/kg of feed). On the 32nd day, the fish were infekted with A. hydrophila at a density of 108 CFU/mL of 0.1 mL/fish intramuscularly, then reared up to 46 days. The results shown that there was an effect of adding fermented red ginger in the feed on the hematology of striped catfish before and after the challenge test with A. hydrophila. The best dose was P2 (175 mL/kg) with a total erythrocyte range of 2.31 x 106 cells/mm3, hematocrit was 39.33%, hemoglobin was 10.40 g/dL, total leukocytes was 11.12 x 104 cells/mm3, survival rate 93.33%, absolute weight growth 19.34 g and water quality during temperature ranged from 28.3-29.2oC, pH 6-7, DO 4.7-5.5 mg/L, and NH3 0.002-0.003 mg/L.